A comprehensive evaluation model based on fuzzy meta-association rules. (2nd September 2019) - Hao-Yun, Qian
At present, the attention to the competitiveness of the provincial-level administrative region has become a hot topic. Based on principles of scientificity, systematicness, comparability and feasibility, this paper establishes a set of index systems for comprehensively evaluating the comprehensive competitiveness of the provincial-level administrative region, and proposes a kind of fuzzy meta-association rule method based on hierarchy theory. It carries out binary fusion extraction of the meta-rule for urban development evaluation element knowledge by making use of the similar structure of the data stored by development branch in each city, with no need to process the entire data set. It is allowed to obtain results/modes from single database to reduce the time required for rule mining. Finally, the comprehensive competitiveness level of the provincial-level administrative regions all over the country is analysed and evaluated from the microcosmic level and macroscopic level through factor analysis and clustering analysis.